Fe-Cr-Ni alloy having excellent workability and high-temperature strength

By optimizing the composition of Fe-Cr-Ni alloys, the problem of difficult to take into account both the room temperature strength and the processing performance of the existing alloys when improving the high temperature strength is solved, and the excellent performance of the alloys at room temperature and high temperature is achieved, and the demand of the reaction towers in high pressure and high temperature environments is met.

CN119731359APending Publication Date: 2025-03-28NIPPON YAKIN IND KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380059966.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-15
Filing Date
2023-05-01
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When the existing Fe-Cr-Ni-based alloys increase the high-temperature strength, the room temperature strength and processing performance are difficult to take into account, and the corrosion resistance and high-temperature elongation are insufficient, which cannot meet the needs of the reaction tower in high-pressure and high-temperature environment.

Method used

By optimizing the alloy composition, the content of C is ensured to be within the range of 0.03-0.08%, the content of Ni is within the range of 35.5-45.5%, and the content of Cr is within 23.5-26.0%, and the content of elements such as Nb, N, Ti, B, and P is controlled to achieve excellent normal temperature and high temperature performance.

Benefits of technology

It realizes excellent yield strength and elongation of the alloy at room temperature and high temperature, improves processing performance and high temperature characteristics, and meets the needs of the reaction tower in high pressure and high temperature environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731359A_ABST
    Figure CN119731359A_ABST
Patent Text Reader

Abstract

Provided is an Fe-Cr-Ni alloy having excellent workability and high-temperature characteristics. A Fe-Cr-Ni alloy which contains, in mass%, 0.03 to 0.08% of C, 0.10 to 0.50% of Si, 0.20 to 1.20% of Mn, 0.001 to 0.040% of P, 0.0001 to 0.0030% of S, 35.5 to 45.5% of Ni, 23.5 to 26.0% of Cr, 0.30 to 1.50% of Mo, 0.01 to 0.30% of Cu, 0.010 to 0.150% of Al, 0.10% or less of Ti, 0.0005 to 0.0050% of B, 0.02 to 0.30% of Co, 0.45 to 0.60% of Nb, and 0.15 to 0.30% of N, with the remainder being Fe and unavoidable impurities, and which has a 0.2% yield strength of 400 MPa or less in a normal temperature tensile test, an elongation of 40.0% or more, a 0.2% yield strength of 140 MPa or more in a high
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a Fe-Cr-Ni alloy that can be used as a structural material for a reaction tower that requires excellent high-temperature strength. Specifically, the present invention relates to a technology that optimizes the composition during alloy production to achieve excellent yield strength and elongation at both room temperature and high temperature. Background Art

[0002] In recent years, clean energy using solar power generation has attracted much attention. In particular, in order to prevent global warming, the attention has increased year by year in terms of not releasing carbon dioxide. When manufacturing solar power generation equipment, polysilicon that is purified from crude silicon is often used as the raw material for power generation elements. Inside the reaction tower used to purify the polysilicon, the pressure of the reaction gas is as high as 100MPa or more, and the temperature is as high as 1100°F or more, and the environment is very harsh. The materials used for the reaction tower are required to have not only excellent processability and corrosion resistance, but also excellent high-temperature strength. If the high-temperature strength is insufficient, the service life of the reaction tower will be shortened and production efficiency will be greatly reduced. In order to meet such characteristic requirements, suitable Fe-Cr-Ni alloys are required.

[0003] However, if the high temperature strength is improved, the room temperature strength will also increase, making the material processing more difficult when manufacturing the reaction tower. In addition, since the above-mentioned reaction gas is a corrosive gas containing chlorine, excellent corrosion resistance is also required, so Fe-Cr-Ni alloys with excellent corrosion resistance, excellent abnormal temperature processing performance and high temperature strength are required.

[0004] As a prior art focusing on high temperature strength, Patent Document 1 discloses a ferritic stainless steel having excellent high temperature oxidation resistance, high temperature creep strength, and high temperature tensile strength. However, there is no specified value related to the high temperature elongation in the claims, and the value of the yield strength of the high temperature tensile strength described in the examples is also low.

[0005] In addition, Patent Document 2 discloses a Ni-based alloy and a method for producing a Ni-based alloy material having excellent structural stability and high-temperature strength. However, the Ni-based alloy requires the addition of expensive elements such as Mo and W, which increases the cost.

[0006] Also, Patent Document 3 proposes an Fe-Cr-Ni alloy that achieves high creep rupture properties by controlling the composition and precipitates or crystals during alloy manufacturing, but there is no description of the room temperature strength, grain size, high temperature 0.2% yield strength, and high temperature elongation, and the alloy is not designed with processability in mind.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2016-079437

[0010] Patent Document 2: Japanese Patent Application Publication No. 2008-297579

[0011] Patent Document 3: Japanese Patent No. 6675846 Summary of the invention

[0012] Problems to be solved by the invention

[0013] The present invention has been made in view of the above-mentioned problems in the prior art, and an object of the present invention is to provide a Fe-Cr-Ni alloy having excellent processing performance and high temperature characteristics.

[0014] Solutions to Solve Problems

[0015] In order to solve the above problems, the inventors have repeatedly studied. First, weigh the raw materials such as electrolytic iron, Cr, Mo, and Ni, and melt them in a high-frequency induction furnace. The crucible is magnesium oxide, and the melting amount is 20kg. Here, the concentration of each element such as Ni is appropriately adjusted for experimental testing. After melting, pour it into a mold, then forge it into a thickness of 20mm, and anneal it at 1300℃ for 20 to 60min.

[0016] According to ASTM E8 standard, round bar test pieces for room temperature tensile test were prepared from the annealed sheets, and then tensile tests were performed according to ASTM E8 standard to evaluate 0.2% yield strength and elongation.

[0017] According to ASTM E8 standard, round bar test pieces for high temperature tensile test were prepared from annealed plates. Then, high temperature tensile test was carried out at 1100°F according to ASTM E21 standard to evaluate 0.2% yield strength and elongation.

[0018] The grain size was measured as follows: a sample of 5 mm×20 mm×15 mm was cut from the annealed sheet, and the cross section perpendicular to the forging direction was mirror-polished and then microscopically observed using an optical microscope in accordance with ASTM E112 to measure the average grain size.

[0019] In the test of measuring the number of carbonitrides of NbN, NbC, TiN, and TiC and the precipitate distribution of NbN, NbC, TiN, TiC, and M23C6, a 5mm×10mm×10mm sample was first cut from the 1 / 4 position of the thickness of the above-mentioned annealed plate, and the cross-section perpendicular to the forging direction was mirror-polished, and then observed and analyzed by SEM-EDS.

[0020] In the hardness test, a 20 mm × 50 mm × 50 mm specimen was first cut from the annealed sheet surface, the surface was ground to 320 grit sandpaper, and then the hardness was measured by a Brinell hardness test using a specified super-hard alloy ball according to the ASTM E10 standard.

[0021] In this way, an alloy that ensures appropriate processing properties and high temperature strength is determined by determining an appropriate alloy component range.

[0022] The Fe-Cr-Ni alloy of the present invention is characterized in that it contains, by mass%, C: 0.03-0.08%, Si: 0.10-0.50%, Mn: 0.20-1.20%, P: 0.001-0.040%, S: 0.0001-0.0030%, Ni: 35.5-45.5%, Cr: 23.5-26.0%, Mo: 0.30-1.50%, Cu: 0.01-0.30%, Al: 0.010-0.150%, Ti: 0.10% or less, B: 0.0005-0.0050%, Co: 0.02-0.30%, Nb: 0.45-0.60% and N: 0.15-0.30%, and the remainder is composed of Fe and inevitable impurities, ASTM The 0.2% yield strength of the room temperature tensile test specified in E8 meets the value of 400MPa or less and the elongation meets the value of 40.0% or more. The 0.2% yield strength of the high temperature tensile test at 1100°F specified in ASTM E21 meets the value of 140MPa or more and the elongation meets the value of 50.0% or more. The average grain size of the microscope test specified in ASTM E112 meets the value of -3 to 6. For one or more of NbN, NbC, TiN, and TiC with a major diameter of 0.5 to 5μm, their total must contain an average of 20 to 180 pieces / mm in any cross section. 2 In addition, when one or more of NbN, NbC, TiN, and TiC with a major diameter exceeding 5 μm are included, the total number of such NbN, NbC, TiN, and TiC is 5.0 pieces / mm on average in any cross section. 2 the following.

[0023] The present invention is characterized in that the mass % of each component is adjusted to 0.120≤Nb×N+Nb×C+Ti×N+Ti×C≤0.150.

[0024] The present invention is characterized in that in the Fe-Cr-Ni alloy, the mass % of each component is adjusted to 0.0020%≤B+P≤0.0400%, and for one or more of NbN, NbC, TiN, TiC, and M23C6 with a major axis of 0.5 to 5 μm, the total proportion of precipitates precipitated at the grain boundaries on any cross section is 10 to 30% in terms of number ratio.

[0025] The present invention is characterized in that the hardness test value when using a cemented carbide ball having the Brinell hardness specified in ASTM E10 is 130 to 210.

[0026] Brief description of the attached figure

[0027] Figure 1 This is an electron micrograph showing a typical NbC precipitate observed in the measurement of the number of precipitates in the present invention.

[0028] Figure 2 This is an electron micrograph showing the grain boundary precipitates and intragranular precipitates of Inventive Example 17 in the Examples. The blue dots are precipitates precipitated at the grain boundary, and the red dots are precipitates precipitated within the grains. DETAILED DESCRIPTION

[0029] The present invention is a Fe-Cr-Ni alloy, which contains, in terms of mass%, C: 0.03-0.08%, Si: 0.10-0.50%, Mn: 0.20-1.20%, P: 0.001-0.040%, S: 0.0001-0.0030%, Ni: 35.5-45.5%, Cr: 23.5-26.0%, Mo: 0.30-1.50%, Cu: 0.01-0.30%, A1: 0.01-0.15%, Ti: 0.10% or less, B: 0.0005-0.0050%, Co: 0.02-0.30%, Nb: 0.45-0.60% and N: 0.15-0.30% in order to improve the workability and high temperature characteristics of the Fe-Cr-Ni alloy, and the remainder is composed of Fe and inevitable impurities. The reason for limiting to this range will be described.

[0030] C: 0.03~0.08%

[0031] C is an element required to ensure the 0.2% yield strength of the alloy at room temperature and high temperature. If it is less than 0.03%, the required strength cannot be obtained. On the other hand, if it exceeds 0.08%, the number of NbC and TiC increases, and the 0.2% yield strength at room temperature becomes too high. Therefore, the C content is determined to be 0.03-0.08%. It is preferably 0.035-0.075%, and more preferably 0.04-0.07%.

[0032] Si: 0.10~0.50%

[0033] Si is added as a deoxidizer, and is an element necessary to ensure oxidation resistance at high temperatures. When it is less than 0.10%, sufficient effects cannot be obtained. On the other hand, if it exceeds 0.50%, the stability of the austenite phase decreases, and the required high temperature 0.2% yield strength cannot be obtained, so it is determined to be 0.10-0.50%. It is preferably 0.12-0.45%, and more preferably 0.13-0.40%.

[0034] Mn: 0.20~1.20%

[0035] Mn is added as a deoxidizer and is an element that stabilizes the austenite phase. When it is less than 0.20%, sufficient effect cannot be obtained. On the other hand, if it exceeds 1.20%, the stability of the austenite phase decreases and the required high temperature 0.2% yield strength cannot be obtained, so it is determined to be 0.20-1.20%. It is preferably 0.35-1.10%, and more preferably 0.50-1.00%.

[0036] P: 0.001~0.040%

[0037] P is an important element in the present invention and an impurity element that is inevitably mixed into steel. If the content is too high, it will segregate at the grain boundary and reduce the high temperature elongation. Therefore, its upper limit needs to be strictly limited. In the present invention, P is limited to less than 0.040%. The preferred upper limit of the content is 0.030%, and the more preferred upper limit is 0.020%. The closer the lower limit of the P content is to 0%, the more preferred, but based on Invention Example 1, 0.001% can be cited.

[0038] S: 0.0001~0.0030%

[0039] S is an important element in the present invention, and it forms sulfides to reduce toughness. Therefore, the S content is preferably as small as possible, and the upper limit is preferably 0.0030%. It is preferably 0.0015% or less, and more preferably 0.0010%. However, S is an element that can greatly improve the fluidity of the molten liquid during melting and improve weldability even if the content is small. Therefore, although S is not particularly limited, it is preferably contained in an amount of 0.0001% or more from the viewpoint of obtaining good weldability. It should be noted that the S content is adjusted to the range of the present invention by adding Al and Si for desulfurization.

[0040] Ni: 35.5~45.5%

[0041] Ni is an important element for stabilizing the austenite phase and maintaining the high temperature 0.2% yield strength. If it is less than 35.5%, the effect cannot be obtained, and if it exceeds 45.5%, the raw material cost becomes high. Therefore, it is determined to be 35.5-45.5%. It is preferably 36.0-44.0%, and more preferably 37.0-40.0%.

[0042] Cr: 23.5~26.0%

[0043] Cr is an element that improves corrosion resistance and has the effect of forming a dense oxide film at high temperature and maintaining the high temperature 0.2% yield strength of the base material. When it is less than 23.5%, the effect cannot be obtained. On the other hand, if it exceeds 26.0%, the stability of the austenite phase decreases and the required high temperature 0.2% yield strength cannot be obtained. Therefore, it is determined to be 23.5-26.0%. It is preferably 24.0-25.5%, and more preferably 24.5-25.4%.

[0044] Mo: 0.30~1.50%

[0045] Mo is an element that improves corrosion resistance and has a grain boundary strengthening effect. It is also an element required to ensure high temperature 0.2% yield strength. When it is less than 0.30%, its effect cannot be obtained. On the other hand, if it exceeds 1.50%, σ phase precipitates and high temperature elongation decreases. Therefore, it is determined to be 0.30-1.50%. It is preferably 0.35-1.30%, and more preferably 0.40-1.00%.

[0046] Cu: 0.01~0.30%

[0047] Cu is an element that stabilizes the austenite phase and improves the room temperature elongation, and is an essential element for the alloy of the present invention. In order to obtain its effect, it is necessary to contain more than 0.01%. On the other hand, if the content of Cu increases, the high temperature 0.2% yield strength will decrease. Therefore, the upper limit of the content of Cu is set to 0.30%. Preferably, it is 0.02 to 0.25%, and more preferably 0.03 to 0.20%.

[0048] Al: 0.010~0.150%

[0049] Al is a useful element for making the oxide scale after rolling denser. From this point of view, it is necessary to add 0.010%. Furthermore, it is also an effective element as a deoxidizer. When it is less than 0.010%, sufficient effect cannot be obtained, oxide inclusions increase, and sufficient high-temperature 0.2% yield strength cannot be obtained. In addition, if it exceeds 0.150%, Al nitride is formed due to combination with N, so the high-temperature 0.2% yield strength decreases. Therefore, it is determined to be 0.010-0.150%. It is preferably 0.015-0.130%, and more preferably 0.020-0.100%.

[0050] Ti: 0.10% or less

[0051] Ti is useful for forming nitrides and carbides to ensure high temperature 0.2% yield strength, so it can be added. Addition of more than 0.10% will increase the number of nitrides or carbides, which is beyond the scope of the present invention. Therefore, the addition should be controlled to 0.10% or less. Preferably, it is 0.07% or less, and more preferably, it is 0.05% or less.

[0052] B: 0.0005~0.0050%

[0053] B is an element segregating at the grain boundary, and has the effect of improving the grain boundary strength at high temperature. It is an important element for ensuring the high temperature 0.2% yield strength. When it is less than 0.0005%, its effect cannot be obtained, and when it exceeds 0.0050%, the high temperature elongation decreases. Therefore, it is determined to be 0.0005-0.0050%. It is preferably 0.0010-0.0045%, and more preferably 0.0015-0.0040%.

[0054] Co: 0.02~0.30%

[0055] Co is a useful element that does not change the strength at room temperature but only increases the high temperature 0.2% yield strength. It is an essential element for the alloy of the present invention. When it is less than 0.02%, its effect cannot be obtained. If it exceeds 0.30% and is added, the high temperature elongation decreases. In addition, the raw material cost becomes high. Therefore, it is determined to be 0.02-0.30%. It is preferably 0.03-0.28%, and more preferably 0.04-0.25%.

[0056] Nb: 0.45~0.60%

[0057] Nb is useful for forming nitrides and carbides to ensure high temperature 0.2% yield strength. When it is less than 0.45%, its effect cannot be obtained. However, adding more than 0.60% will increase the number of nitrides or carbides, thereby reducing the high temperature 0.2% yield strength. Therefore, it is determined to be 0.45-0.60%. It is preferably 0.47-0.58%, and more preferably 0.50-0.56%.

[0058] N: 0.15~0.30%

[0059] N is an element that improves corrosion resistance and is also an element useful for forming nitrides with Nb and Ti. When it is less than 0.15%, a sufficient effect cannot be obtained, and the required room temperature 0.2% yield strength and high temperature 0.2% yield strength cannot be obtained. On the other hand, if it exceeds 0.30%, the number of nitrides or carbides increases, which exceeds the scope of the present invention and makes the room temperature 0.2% yield strength too high. Therefore, it is determined to be 0.15 to 0.30%. It is preferably 0.17 to 0.28%, and more preferably 0.20 to 0.25%.

[0060] By satisfying the above composition range, the 0.2% yield strength value of the room temperature tensile test specified in ASTM E8 can be satisfied to be below 400 MPa. If it exceeds 400 MPa, the processability is poor and the production of the reaction tower will be difficult. It is preferably below 390 MPa, and more preferably below 380 MPa.

[0061] In addition, by satisfying the above-mentioned component range, the value of the elongation of the room temperature tensile test specified in ASTM E8 can be satisfied to be 40.0% or more. If it is less than 40.0%, the processability is poor and it is not suitable for the preparation of a reaction tower. It is preferably 42.0% or more, and more preferably 43.0% or more.

[0062] In addition, by satisfying the above-mentioned composition range, the 0.2% yield strength of the high temperature tensile test at 1100°F specified in ASTM E21 can be satisfied to be 140 MPa or more. If it is less than 140 MPa, cracks will occur in the above-mentioned high temperature environment, so it is not suitable for use of the alloy. It is preferably 150 MPa or more, and more preferably 160 MPa or more.

[0063] In addition, by satisfying the above-mentioned composition range, the elongation of the high temperature tensile test specified in ASTM E21 can be satisfied to be 50.0% or more. If it is less than 50.0%, cracks will occur in the above-mentioned high temperature environment, so it is not suitable for use of the alloy. It is preferably 55.0% or more, and more preferably 60.0% or more.

[0064] In addition, by satisfying the above-mentioned components, the average grain size of the microscope test specified in ASTM E112 can meet -3 to 6. If it is less than -3, the grains are coarse and the high temperature 0.2% yield strength is reduced. If it exceeds 6, the room temperature 0.2% yield strength becomes high and the workability is poor, so it is not suitable for the production of a reaction tower. It is preferably -2 to 5, and more preferably -1 to 4.

[0065] In addition, by satisfying the above-mentioned composition range, it is shown that one or more of NbN, NbC, TiN, and TiC having a major diameter of 0.5 to 5 μm must contain an average of 20 to 180 particles / mm in total on any cross section. 2 In the case of containing one or more of NbN, NbC, TiN, and TiC with a major diameter exceeding 5 μm, the total number of these is an average of 5.0 pieces / mm in any cross section. 2 If one or more of NbN, NbC, TiN and TiC with a major diameter of 0.5 to 5 μm are present, the total number of these is less than 20 pieces / mm on average in any cross section. 2, the grains coarsen during annealing and cannot meet the high temperature 0.2% yield strength. If one or more of NbN, NbC, TiN, and TiC with a long diameter of 0.5 to 5 μm, their total number exceeds an average of 180 / mm on any cross section 2 , or when containing one or more of NbN, NbC, TiN, and TiC with a major diameter exceeding 5 μm, the total number of these exceeds an average of 5.0 pieces / mm in any cross section 2 , then carbonitrides become the starting point of voids, and the high-temperature elongation decreases. It is preferred that an average of 30 to 170 precipitates of one or more of NbN, NbC, TiN, and TiC containing 0.5 to 5 μm, and an average of 3.0 precipitates / mm of one or more of NbN, NbC, TiN, and TiC with a long diameter exceeding 5 μm 2 More preferably, an average of 40 to 160 precipitates containing one or more of NbN, NbC, TiN, and TiC of 0.5 to 5 μm are required, and an average of 1.0 precipitates / mm are required for one or more of NbN, NbC, TiN, and TiC with a major diameter exceeding 5 μm. 2 the following.

[0066] 0.120≤Nb×N+Nb×C+Ti×N+Ti×C≤0.150···(Formula 1)

[0067] Formula 1 represents the range of the amount of carbonitride precipitation. If it is less than 0.120, the precipitation of carbonitride is small, the grains are coarsened during annealing, and a good high-temperature 0.2% yield strength cannot be obtained. If it exceeds 0.150, the carbonitride becomes the starting point of the void and the high-temperature elongation becomes low. It is preferably 0.125 to 0.145, and more preferably 0.130 to 0.140.

[0068] 0.0020%≤B+P≤0.0400%...(Formula 2)

[0069] Formula 2 represents the range of good addition amount of elements segregated at grain boundaries. If it is less than 0.0020%, the segregation amount at the grain boundaries is insufficient, the grain boundaries are not strengthened, and good high temperature 0.2% yield strength cannot be obtained. If it exceeds 0.0400%, the segregation amount at the grain boundaries becomes too much, so the grain boundaries become brittle and the high temperature elongation decreases. It is preferably 0.0025% to 0.0300%, and more preferably 0.0030% to 0.0200%.

[0070] In addition, in the Fe-Cr-Ni alloy, it is characterized in that for one or more of NbN, NbC, TiN, TiC, and M23C6 with a long diameter of 0.5 to 5 μm, the proportion of precipitates precipitated at the grain boundary on any cross section is 10 to 30% in total. If it is less than 10%, the high temperature 0.2% yield strength cannot be obtained, and if it exceeds 30%, the high temperature elongation is not satisfied. It is preferably 12 to 28%, and more preferably 15 to 25%.

[0071] In addition, the hardness test value when tested using a super-hard alloy ball of Brinell hardness specified in ASTM E10 is 130 to 210. If it is less than 130, the high temperature 0.2% yield strength cannot be obtained, and if it exceeds 210, the workability is poor and it is not suitable for the production of a reaction tower. It is preferably 140 to 200, and more preferably 150 to 190.

[0072] Example

[0073] Raw materials such as iron scraps, chromium-iron alloy, nickel-iron alloy, stainless steel scraps, etc. adjusted in a certain ratio are put into an electric arc furnace for melting, and secondary refining is carried out in an AOD (Argon Oxygen Decarburization) furnace or a VOD (Vacuum Oxygen Decarburization) furnace. After adjusting the main component composition shown in Table 1, continuous casting is performed to form a steel sheet (steel billet). It should be noted that the composition of C and S shown in the table is the value obtained by analysis using a carbon / sulfur simultaneous analysis device (combustion in oxygen flow-infrared absorption method), the composition of N is the value obtained by analysis using an oxygen / nitrogen simultaneous analysis device (inert gas-pulse heating melting method), and the composition other than the above is the value obtained by analysis using a fluorescent X-ray analysis. Next, the above-mentioned steel billet is hot rolled and annealed at 1180°C to 1300°C to obtain a hot-rolled annealed steel sheet with a thickness of 20 mm.

[0074] Table 1

[0075]

[0076] In the evaluation of room temperature tensile strength, firstly, the long axis of the sample is cut in the direction perpendicular to the rolling direction of the hot-rolled annealed steel sheet, and a round bar sample is made according to ASTM E8, and then a tensile test is carried out according to ASTM E8 to measure the 0.2% yield strength and elongation. The case where the 0.2% yield strength satisfies 380 MPa or less and the elongation satisfies 43.0% or more is evaluated as ◎, the case where the 0.2% yield strength satisfies 390 MPa or less and the elongation satisfies 42.0% or more is evaluated as O, the case where the 0.2% yield strength satisfies 400 MPa or less and the elongation satisfies 40.0% or more is evaluated as Δ, and the case where the 0.2% yield strength does not satisfy 400 MPa or less and the elongation does not satisfy 40.0% or more is evaluated as ×, as shown in Table 2.

[0077] In the evaluation of high temperature tensile strength, first, the long axis of the sample is cut in the direction perpendicular to the rolling direction of the hot-rolled annealed steel sheet, and a round bar sample is made according to ASTM E8. Then, the sample is subjected to a high temperature tensile test at 1100°F specified in ASTM E21 to measure the 0.2% yield strength, tensile strength, and elongation. The case where the 0.2% yield strength satisfies 160MPa or more and the elongation satisfies 60.0% or more is evaluated as ◎, the case where the 0.2% yield strength satisfies 150MPa or more and the elongation satisfies 55.0% or more is evaluated as ○, the case where the 0.2% yield strength satisfies 140MPa or more and the elongation satisfies 50.0% or more is evaluated as Δ, and the case where the 0.2% yield strength does not satisfy 140MPa or more and the elongation does not satisfy 50.0% or more is evaluated as ×, as shown in Table 2.

[0078] In the evaluation of the average grain size, the hot-rolled annealed sheet was first cut and mirror-polished at 0.16 mA / mm. 2 Oxalic acid electrolytic corrosion was carried out under the conditions. The microscope test specified in ASTM E112 was carried out on the sample by the comparison method. The case of satisfying -1 to 4 was evaluated as ◎, the case of satisfying -2 to 5 was evaluated as ○, the case of satisfying -3 to 6 was evaluated as Δ, and the case of not satisfying -3 to 6 was evaluated as ×, as shown in Table 2.

[0079] In the evaluation of carbonitrides of NbN, NbC, TiN, and TiC, the above-mentioned hot-rolled annealed sheet is first cut, mirror-polished, and then observed and analyzed by SEM-EDS. 100 photos are taken at a magnification of 10,000 times, and the average number is calculated. Furthermore, the chemical composition is determined by EDS. At this magnification, carbonitrides as small as 0.5 μm can be visually observed, so in the present invention, 0.5 μm is set as the lower limit. The number of carbonitrides with a long diameter of 0.5 to 5 μm is an average of 40 to 160 pieces / mm 2 The average number of carbonitrides with a long diameter exceeding 5 μm satisfies 0 to 1.0 per mm.2 The case of ◎ was evaluated as ◎, and the average number of carbonitrides with a major diameter of 0.5 to 5 μm was 30 to 170 pieces / mm 2 The average number of carbonitrides with a long diameter exceeding 5 μm satisfies the requirement of greater than 1.0 to 3.0 per mm. 2 The case of 0 was evaluated as ○, and the average number of carbonitrides with a major diameter of 0.5 to 5 μm was 20 to 180 pieces / mm 2 The average number of carbonitrides with a long diameter exceeding 5 μm satisfies the requirement of greater than 3.0 to 5.0 per mm. 2 The case where the average number of carbonitrides with a major diameter of 0.5 to 5 μm does not meet the requirement of 20 to 180 pieces / mm is evaluated as Δ. 2 , or the average number of carbonitrides with a major diameter exceeding 5 μm exceeds 5.0 pieces / mm 2 The cases where the defects were found were evaluated as ×, as shown in Table 2.

[0080] The evaluation of Formula 1 was shown in Table 3: the case where 0.130 to 0.140 was satisfied was evaluated as ◎, the case where 0.125 to 0.145 was evaluated as O, the case where 0.120 to 0.150 was evaluated as Δ, and the case where 0.120 to 0.150 was not satisfied was evaluated as ×.

[0081] Regarding the evaluation of Formula 2, the case satisfying 0.0030% to 0.0200% was evaluated as ◎, the case satisfying 0.0025% to 0.0300% was evaluated as ○, the case satisfying 0.0020% to 0.0400% was evaluated as Δ, and the case not satisfying 0.0020% to 0.0400% was evaluated as ×, as shown in Table 3.

[0082] For the evaluation of the precipitate distribution of NbN, NbC, TiN, TiC, and M23C6, the above-mentioned hot-rolled annealed sheet was first cut, mirror-polished, and then observed and analyzed by SEM-EDS. 100 photos were taken at a magnification of 1000 times to determine the average distribution. Furthermore, the chemical composition was determined by EDS. The case where the proportion of precipitates precipitated at the grain boundary meets 15-25% is evaluated as ◎, the case where it meets 12-28% is evaluated as ○, the case where it meets 10-30% is evaluated as Δ, and the case where it does not meet 10-30% is evaluated as ×, as shown in Table 3.

[0083] For the evaluation of hardness, the hot-rolled annealed sheet was first cut and sampled, and the surface was then ground with 320-grit sandpaper, and then the Brinell hardness test using a superhard alloy ball specified in ASTM E10 was performed. The case where the hardness satisfied 150 to 190 was evaluated as ◎, the case where the hardness satisfied 140 to 200 was evaluated as ○, the case where the hardness satisfied 130 to 210 was evaluated as Δ, and the case where the hardness did not satisfy 130 to 210 was evaluated as ×, as shown in Table 3.

[0084] As a comprehensive evaluation, if the evaluation of the composition, 0.2% yield strength at room temperature, elongation at room temperature, 0.2% yield strength at high temperature, elongation at high temperature, average grain size, and number of precipitates recorded in claim 1 is ◎, ○, or Δ, then the evaluation is ○. If one or more are ×, then the evaluation is ×, as shown in Table 3.

[0085] Table 2

[0086]

[0087]

Table 3

[0088]

[0089] The inventive examples all satisfy the scope of the invention of this application, and thus satisfy the room temperature strength and high temperature strength, grain size, and number of carbonitrides.

[0090] In sample No. 18, since S exceeded the upper limit, a large amount of sulfides were formed, and the high temperature 0.2% yield strength and high temperature elongation did not satisfy the specified values.

[0091] Sample No. 19 has B and P exceeding the upper limit, so the grain boundary is embrittled, and the room temperature elongation, high temperature 0.2% yield strength and high temperature elongation do not meet the specified values. In addition, the values ​​of equations 1 and 2 exceed the upper limit, and the grain boundary precipitation ratio of the precipitate does not meet the lower limit.

[0092] In sample No. 20, since N and Nb exceeded the upper limit, a large amount of nitrides precipitated, and the room temperature 0.2% yield strength, high temperature elongation, number of precipitates, and grain size did not meet the specified values. In addition, the value of formula 1 exceeded the upper limit.

[0093] In sample No. 21, since C and Ti exceeded the upper limit, a large amount of carbides precipitated, and the high temperature elongation, the number of precipitates, and the grain size did not meet the specified values. In addition, the value of Formula 1 exceeded the upper limit.

[0094] Since the Co content of sample No. 22 did not satisfy the lower limit, the high-temperature strength was not enhanced, and the high-temperature 0.2% yield strength and high-temperature elongation did not satisfy the specified values.

[0095] Sample No. 23 does not satisfy the lower limits of Nb and N, so the nitride content is small, and the lower limits of the high temperature 0.2% yield strength, the number of precipitates, the grain size, and the hardness test do not satisfy the specified values. In addition, the value of Formula 1 does not satisfy the lower limit.

[0096] Sample No. 24 does not meet the lower limit of C, so there are few carbides and the high temperature 0.2% yield strength does not meet the specified value. In addition, the value of Formula 1 does not meet the lower limit. Cu also exceeds the upper limit and does not meet the lower limit of the hardness test.

[0097] Sample No. 25 has high room temperature strength because C exceeds the upper limit and Cu does not meet the lower limit, so the room temperature 0.2% yield strength and room temperature elongation do not meet the specified values. B also does not meet the lower limit, so the high temperature 0.2% yield strength does not meet the specified value. In addition, the value of formula 2 does not meet the lower limit, and the hardness test value also exceeds the upper limit.

[0098] In sample No. 26, B does not satisfy the lower limit, so the grain boundaries are not strengthened and the high temperature 0.2% yield strength does not satisfy the specified value. In addition, the value of Formula 2 does not satisfy the upper limit, and the grain boundary precipitation ratio of precipitates is low.

[0099] Sample No. 27 does not satisfy the lower limits of C and Nb, so there are few carbides, and the high temperature 0.2% yield strength, the number of precipitates, and the grain size do not satisfy the specified values. In addition, the value of Formula 1 does not satisfy the lower limit.

[0100] Since the Co content of sample No. 28 exceeded the upper limit, the high temperature elongation did not satisfy the specified value.

Claims

1. A Fe-Cr-Ni alloy, characterized in that: Contains, by mass%, C: 0.03-0.08%, Si: 0.10-0.50%, Mn: 0.20-1.20%, P: 0.001-0.040%, S: 0.0001-0.0030%, Ni: 35.5-45.5%, Cr: 23.5-26.0%, Mo: 0.30-1.50%, Cu: 0.01-0.30%, Al: 0.010-0.150%, Ti: 0.10% or less, B: 0.0005-0.0050%, Co: 0.02-0.30%, Nb: 0.45-0.60% and N: 0.15-0.30%, with the remainder being Fe and inevitable impurities, ASTM The 0.2% yield strength of the room temperature tensile test specified in E8 meets the value of 400MPa or less and the elongation meets the value of 40.0% or more, the 0.2% yield strength of the high temperature tensile test at 1100°F specified in ASTM E21 meets the value of 140MPa or more and the elongation meets the value of 50.0% or more, the average grain size of the microscope test specified in ASTM E112 meets the value of -3 to 6, and for one or more of NbN, NbC, TiN, and TiC with a major diameter of 0.5 to 5μm, their total must contain an average of 20 to 180 pieces / mm in any cross section 2 In addition, when one or more of NbN, NbC, TiN, and TiC having a major diameter exceeding 5 μm are included, the total number of these is an average of 5.0 pieces / mm in any cross section. 2 the following.

2. The Fe-Cr-Ni alloy according to claim 1, characterized in that: The mass % of each component is adjusted to 0.120≤Nb×N+Nb×C+Ti×N+Ti×C≤0.

150.

3. The Fe-Cr-Ni alloy according to claim 1, characterized in that: The mass % of each component is adjusted to 0.0020%≤B+P≤0.0400%. For one or more of NbN, NbC, TiN, TiC, and M23C6 with a long diameter of 0.5 to 5 μm, the proportion of precipitates precipitated at the grain boundaries on any cross section in their total is 10 to 30% in terms of number ratio.

4. The Fe-Cr-Ni alloy according to claim 2, characterized in that: The mass % of each component is adjusted to 0.0020%≤B+P≤0.0400%. For one or more of NbN, NbC, TiN, TiC, and M23C6 with a long diameter of 0.5 to 5 μm, the proportion of precipitates precipitated at the grain boundaries on any cross section in their total is 10 to 30% in terms of number ratio.

5. The Fe-Cr-Ni alloy according to claim 1, characterized in that: The value of the Brinell hardness test using a cemented carbide ball specified in ASTM E10 is 130 to 210.

6. The Fe-Cr-Ni alloy according to claim 2, characterized in that: The Brinell hardness test value using a cemented carbide ball specified in ASTM E10 is 130 to 210.

7. The Fe-Cr-Ni alloy according to claim 3, characterized in that: The Brinell hardness test value using a cemented carbide ball specified in ASTM E10 is 130 to 210.

8. The Fe-Cr-Ni alloy according to claim 4, characterized in that: The value of the Brinell hardness test using a cemented carbide ball specified in ASTM E10 is 130 to 210.

Citation Information

Patent Citations

  • Nickel-based alloy excellent in structural stability and high tension strength, and method for producing nickel-based alloy material

    JP2008297579A

  • Ferritic stainless steel excellent in high temperature oxidation resistance, high temperature creep strength and high temperature tensile strength

    JP2016079437A